2021
DOI: 10.1108/cg-07-2020-0292
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary appointment of independent directors: evidence from Taiwan

Abstract: Purpose Using a data set of Taiwanese listed firms from 2002 to 2015, this paper aims to examine the determinants to voluntarily appoint independent directors. Design/methodology/approach This study uses panel estimation to exploit both the cross-section and time-series nature of the data. Further, this paper uses Tobit regression, generalized linear model (GLM) in the additional analysis and the two-stage least squares to mitigate for a possible endogeneity issue. Findings The main findings show that Taiw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 86 publications
1
1
0
Order By: Relevance
“…Several studies have shown that the presence of an external director in the board of directors strengthens control over management. This proposal supports the idea that external directors are considered good controllers, acting in the best interests of the firm to develop a good monitoring reputation (Fama, 1980; Fama and Jensen, 1983; Barros et al , 2021; Kao et al , 2021). These directors are considered neutral and can express fully transparent opinions.…”
Section: Theoretical Framework and Research Hypothesessupporting
confidence: 69%
“…Several studies have shown that the presence of an external director in the board of directors strengthens control over management. This proposal supports the idea that external directors are considered good controllers, acting in the best interests of the firm to develop a good monitoring reputation (Fama, 1980; Fama and Jensen, 1983; Barros et al , 2021; Kao et al , 2021). These directors are considered neutral and can express fully transparent opinions.…”
Section: Theoretical Framework and Research Hypothesessupporting
confidence: 69%
“…Also, Jansen (2021) studies the relationship between board processes and board effectiveness. While Calabrese and Manello (2021) consider the impact of the BoD diversity on performance, Kao et al (2021) handle the voluntary appointment of independent board members as an important issue in terms of the CG practices, and Sobhan and Adegbite (2021) examine the determinants of evaluation of the BoD by external parties.…”
Section: Contextual Background and Literature Reviewmentioning
confidence: 99%